The relevance of ecocentrism, personal development and transformational leadership to sustainability and identity - Hay, Robert (Wiley InterScience, 2010)
Identity is formed gradually as we mature through personal development within societal (and natural) context. As such, it is group informed but individually directed and is strongly influenced by our family, community, place and natural surroundings. Together, these interwoven aspects of our lives help us each to create an identity that is unique and that should be able to be sustained over time. However, because we live within collectives and places that have often become less sustainable of late, this has a corresponding effect on our identity. The interactive relationship between identity and sustainability is therefore integral to how we understand and then address issues that currently confront us all. To investigate this relationship, three aspects of identity are considered together: the significance of an ecocentric philosophy, personal development oriented to service and transformational leadership. Interweaving these related reflections goes beyond a more limited view of identity, providing new directions for sustainability. Copyright © 2010 John Wiley & Sons, Ltd and ERP Environment.